Case Report: Successful Immunotherapy Improved the Prognosis of the Unfavorable Subset of Cancer of Unknown Primary - Mei, Jie; Wang, Hao; Fan, Honghong; Ding, Junli; Xu, Junying (Frontiers in Immunology, 2022)
Background: Cancer of unknown primary (CUP) is heterogeneous, and has a wide variety of clinical presentations and a poor prognosis in most patients with median overall survival of only 6 months. The development of molecular profiling contributes to precision therapy, and targeted drugs and immune checkpoint inhibitors (ICIs) greatly promote individualized treatment. Case presentation: Here, we report a case of the unfavorable subset of CUP that has long time survival after the immunotherapy-prominent comprehensive treatment. A 48-year-old man presented with back pain and cough. Diagnostic work-up showed bone marrow, multiple bones, and lymph nodes metastasis. Lymph node pathology implied metastatic poorly differentiated cancer. Next-generation sequencing (NGS) showed no special targets, but the tumor proportion score (TPS) of programmed death-ligand 1 (PD-L1) was 80% and tumor mutation burden (TMB) was 16.7 every million bases. After two cycles of Pembrolizumab 200mg D1 plus nanoparticle albumin-bound (nab)-Paclitaxel 200mg D1&8 (q3w) PET-CT and bone marrow aspiration cytology showed complete response (CR). Subsequently, Pembrolizumab alone was used for three months. Left inguinal lymph nodes showed new metastasis. After two cycles of the combination treatment of Pembrolizumab and (nab)-Paclitaxel, partial response (PR) was achieved. After seven months, retroperitoneal lymph nodes showed new metastasis, and the sequential treatment of radiotherapy and Pembrolizumab exhibited the encouraging efficacy. Up to date, the patient has survived nearly 40 months with the combination therapy. Conclusions: The ICIs-prominent comprehensive treatment provided clinical benefit for the reported case of CUP. Thus, CUP patients with markers of benefiting from immunotherapy should be actively treated with immunotherapy to improve their prognosis.